Antibodies in Sera of Dengue Patients with Plasma Leakage Cross-Reacting with DENV Protein and Endothelial Protein - Dewi Wulandari; Alida Roswita Harahap; Suhendro Suhendro; R. Tedjo Sasmono; Aryati Aryati; Herdiman Theodorus Pohan; Iris Rengganis; Saptawati Bardosono (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Dengue infection remains a major public health problem in Indonesia. Severe dengue associated with plasma leakage require hospitalization and potentially life threatening. However, the mechanism remains unclear, and the occurrence is unpredictable. The role of anti-endothelial antibody is predicted play an important role in the pathogenesis of plasma leakage, as severe dengue is more prevalent in secondary infection or post vaccinated individuals.METHODS: Serum samples from 127 single Dengue Virus (DENV) serotype infected subjects were obtained in day 2 of fever onset. Subjects were divided into plasma leakage and non-plasma leakage based on World Health Organization (WHO) criteria. Anti-endothelial antibody in patient sera were detected using western blot of Human Umbilical Vein Endothelial Cells (HUVEC). To confirm cross-reactivity, the sera was preabsorb with mix-DENV lysate.RESULTS: Three prominent bands were identified on western blot strips that inhibited by pre-absorption with DENV lysate. Plasma leakage patient expressed significantly more antibodies, with 51.7% of plasma leakage patients expressed at least two bands out of those three, compared to 18.5% of non-plasma leakage.CONCLUSION: Antibodies found in sera of dengue patients with plasma leakage cross-reacted with DENV proteins and endothelial proteins 37 kDa, 75 kDa, 120 kDa, and therefore may be involved in the pathogenesis of plasma leakage. Proteomic identification of those protein targets is needed and may be useful for vaccine studies and further development of predictor marker for plasma leakage in dengue.KEYWORDS: severe dengue, plasma leakage, cross-reactive, anti-endothelial antibody.